After the years of lead: notes for the reconciliation of the Basques - Elzo, Javier (Razón y fe, 2018)
Peace in the Basque Country will come and will last to the extent that the perpetrators - those who caused the deaths and indiscriminate suffering of some 42,000 people - and the victims, see the termination of ETA, and when the mistreatment and abuse are publicly recognized, as well as the tortures of those who have suffered in the past and in the present because they are different and, finally, when what grows with peace is the fruit of democracy and civilization and the veil of silence is lifted over all the victims. In short, when there is more humanity in social relations and when a true reconciliation pursued.